Repletion of branched chain amino acids reverses mTORC1 signaling but not improved metabolism during dietary protein dilution - Adriano Maida; Jessica S.K. Chan; Kim A. Sjøberg; Annika Zota; Dieter Schmoll; Bente Kiens; Stephan Herzig; Adam J. Rose (Elsevier, 2017)
Objective: Dietary protein dilution (PD) has been associated with metabolic advantages such as improved glucose homeostasis and increased energy expenditure. This phenotype involves liver-induced release of FGF21 in response to amino acid insufficiency; however, it has remained unclear whether dietary dilution of specific amino acids (AAs) is also required. Circulating branched chain amino acids (BCAAs) are sensitive to protein intake, elevated in the serum of obese humans and mice and thought to promote insulin resistance. We tested whether replenishment of dietary BCAAs to an AA-diluted (AAD) diet is sufficient to reverse the glucoregulatory benefits of dietary PD. Methods: We conducted AA profiling of serum from healthy humans and lean and high fat-fed or New Zealand obese (NZO) mice following dietary PD. We fed wildtype and NZO mice one of three amino acid defined diets: control, total AAD, or the same diet with complete levels of BCAAs (AAD + BCAA). We quantified serum AAs and characterized mice in terms of metabolic efficiency, body composition, glucose homeostasis, serum FGF21, and tissue markers of the integrated stress response (ISR) and mTORC1 signaling. Results: Serum BCAAs, while elevated in serum from hyperphagic NZO, were consistently reduced by dietary PD in humans and murine models. Repletion of dietary BCAAs modestly attenuated insulin sensitivity and metabolic efficiency in wildtype mice but did not restore hyperglycemia in NZO mice. While hepatic markers of the ISR such as P-eIF2α and FGF21 were unabated by dietary BCAA repletion, hepatic and peripheral mTORC1 signaling were fully or partially restored, independent of changes in circulating glucose or insulin. Conclusions: Repletion of BCAAs in dietary PD is sufficient to oppose changes in somatic mTORC1 signaling but does not reverse the hepatic ISR nor induce insulin resistance in type 2 diabetes during dietary PD.